Copyright future, copyright freedom : marking the 40th anniversary of the commencement of Australia's Copyright Act 1968 - Fitzgerald, Brian F.; Atkinson, Benedict A. C. (Sydney University Press, 2011)
This volume offers the thinking and suggestions of some of the finest minds grappling with the future of copyright regulation.
Selection of essays presented at conference held in May 2009 at Old Parliament House, Canberra.
Keywords: Australia. -- Copyright Act 1968.; Copyright Act 1968 (Australia); Copyright -- Australia.; Intellectual property -- Australia.; Droit d'auteur -- Australie.; Propriété intellectuelle -- Australie.; Copyright; Intellectual property; Australia; Electronic books.